2021
DOI: 10.3389/fnut.2021.763677
|View full text |Cite
|
Sign up to set email alerts
|

The Saturation Effect of Body Mass Index on Bone Mineral Density for People Over 50 Years Old: A Cross-Sectional Study of the US Population

Abstract: Background: Previous studies had revealed that Body Mass Index (BMI) positively affected Bone Mineral Density (BMD). However, an excessively high BMI was detrimental to health, especially for the elderly. Moreover, it was elusive how much BMI was most beneficial for BMD in older adults to maintain.Objective: To investigate whether there was a BMI saturation effect value that existed to maintain optimal BMD.Methods: A cross-sectional study was conducted using the datasets of the National Health and Nutrition Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 64 publications
2
25
0
2
Order By: Relevance
“…The WC has been used to assess abdominal obesity, whereas the BMI has been used to assess overall obesity. A cross-sectional research of the American population found a link between BMI and BMD ( 23 ). Another study by Wiacek et al.…”
Section: Discussionmentioning
confidence: 99%
“…The WC has been used to assess abdominal obesity, whereas the BMI has been used to assess overall obesity. A cross-sectional research of the American population found a link between BMI and BMD ( 23 ). Another study by Wiacek et al.…”
Section: Discussionmentioning
confidence: 99%
“…The saturation effect analysis showed that the BMI saturation value was 26.13 (kg/m2) for femur bone and 26.82 (kg/m2) for LS. The results suggest that maintaining a BMI at a slightly overweight level (approximately 26 kg/m2) may obtain optimal BMD [ 34 ]. A study on the relationship between the obesity index and BMD in Chinese people found that BMI levels were positively correlated with LS-BMD in men aged over 60 years [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether from the perspective of reducing other systemic diseases caused by obesity or reducing the incidence of fractures in adolescents, we should find an appropriate BMI while striving for a higher BMD. Ma et al found that, for Americans over 50 years of age, keeping the BMI at a slightly overweight value (about 26 kg/m 2 ) may reduce other adverse effects while obtaining an optimal BMD (44). While in adolescents, BMI saturation values for BMD may change substantially with age, and our findings are the first to investigate BMI saturation values for BMD in US adolescents aged 8-19 years at different ages.…”
Section: B C a Figure 2 | Distribution Histogram Of Bmimentioning
confidence: 58%
“…Ma et al. found that, for Americans over 50 years of age, keeping the BMI at a slightly overweight value (about 26 kg/m 2 ) may reduce other adverse effects while obtaining an optimal BMD ( 44 ). While in adolescents, BMI saturation values for BMD may change substantially with age, and our findings are the first to investigate BMI saturation values for BMD in US adolescents aged 8–19 years at different ages.…”
Section: Discussionmentioning
confidence: 99%